(untitled) (Marketing Journal, 2025)
This scientific work analyzes the specific features of auditing cultural institutions. In particular, the financial, legal and social aspects of the activities of cultural institutions such as theaters are comprehensively considered. The study identifies t he main problems encountered in the audit process, develops practical proposals for their solution and improvement. It also substantiates the need for special approaches, assessment criteria and differential methodology to increase the efficiency of audits in cultural institutions.